Radio over fiber for wireless communications : from fundamentals to advanced topics - Fernando, Xavier N. (Chichester, West Sussex : IEEE/Wiley, 2014)
"This book provides a detailed study of radio over fiber (ROF) based wireless communication systems, otherwise called fiber wireless (Fi-Wi) systems"--
DSP modeling of the ROF link nonlinearity -- Adaptive compensation for the ROF link nonlinearity -- Joint estimation of the fiber wireless channel -- Joint equalization for the Fi-Wi channel -- Performance evaluation of the Hammerstein-type DFE -- Multiuser CDMA Fi-Wi systems -- Fi-Wi for 4G, 5G and OFDM wireless networks.
Includes index.
Machine generated contents note: Foreword ix Preface xi Acknowledgements xv 1 Introduction 1 1.1 Motivation 1 1.2 Basic Fi-Wi System Architecture 10 1.3 Major Issues 12 1.4 Other Fiber Feeder Approaches 13 1.5 Book Outline 14 2 Important Fi-Wi Link Elements 17 2.1 RF-Optical Modulation 17 2.2 The Fiber Channel 29 2.3 Optical Receiver 36 2.4 Brief Review of Baseband-RF Modulation Techniques 40 2.5 The Wireless Channel 42 3 Power Link Budget and Cumulating SNR 49 3.1 Introduction 49 3.2 System Description 50 3.3 Optical Signal to Noise Ratio (OSNR) 51 3.4 Cumulative Signal to Noise Ratio (cSNR) 57 3.5 RAP Design Considerations 58 3.6 Summary 62 4 An Improved Expression for Relative Intensity Noise 63 4.1 Basics 63 4.2 The Fundamental Noise Processes in Radio over Fiber Links 64 4.3 The Signal to Noise Ratio 69 4.4 Numerical Evaluation and Discussion 71 4.5 Summary 72 5 Subcarrier Multiplexed ROF Downlink 75 5.1 Introduction 75 5.2 Background 75 5.3 The ROF Downlink Channel 77 5.4 The Wireless Downlink Channel 91 5.5 Numerical Evaluation and Discussion 92 6 Subcarrier Multiplexed ROF Uplink 97 6.1 The Wireless Uplink Channel 97 6.2 The ROF Uplink Channel 99 6.3 Signals to Distortion, Interference and Noise Ratios 111 6.4 Numerical Evaluations and Discussion 113 6.5 Summary 115 7 Externally Modulated ROF Links 121 7.1 Mach-Zehnder Modulator 121 7.2 Electro-Absorption Modulator (EAM) 125 7.3 Reflective Semiconductor Optical Amplifier (RSOA) 128 7.4 Optimization of the MZI Bias Voltage 128 7.5 Subcarrier Multiplexed Signals in MZI 135 8 DSP Modeling of the ROF Link Nonlinearity 141 8.1 Introduction 141 8.2 Various Attempts to Reduce NLD 142 8.3 DSP Approaches 144 8.4 Basics of DSP for Nonlinear Systems 146 8.5 Baseband Representation of a Passband Complex Nonlinear System 148 8.6 Nonlinear Modeling of Fi-Wi Link 149 9 Adaptive Compensation for the ROF Link Nonlinearity 151 9.1 Adaptive Modeling of the ROF Link 151 9.2 Asymmetric Compensation 159 9.3 Summary 169 10 Joint Estimation of the Fiber Wireless Channel 171 10.1 The Wiener and Hammerstein System Model for Fi-Wi Links 171 10.2 Fiber-Wireless Channel Estimation 172 10.3 Case Study 180 10.4 Summary 182 11 Joint Equalization for the Fiber Wireless Channel 185 11.1 Equalization of the Wireless Channel 185 11.2 Optimization of Polynomial Filter Parameters 189 11.3 Optimization of Linear Filter Parameters 191 11.4 Summary 196 12 Performance Evaluation of the Hammerstein type DFE 197 12.1 Evaluation of the Polynomial Filter 197 12.2 Evaluation of Linear Filters 203 12.3 Case Study 204 12.4 Summary 212 13 Multiuser CDMA Fi-Wi Systems 213 13.1 Multiuser Fi-Wi Uplink Model 213 13.2 Correlation Relationships 215 13.3 ROF Channel Estimation 220 13.4 Case Study 221 13.5 Fiber-Wireless Uplink Equalization 224 13.6 Equalization: Simulation Results and Discussion 225 13.7 Summary 227 14 Fi-Wi for 4G, 5G and OFDM Wireless Networks 229 14.1 Brief History of Cellular Communication Systems 230 14.2 Wireless Access Schemes 232 14.3 Peak to Average Power Ratio Reduction Techniques 235 14.4 OFDM ROF System Improvement 237 14.5 Combinations of OFDMA and CDMA 241 14.6 Summary 242 References 243 References 248 List of Abbreviations 249 .
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: FiWi access networks; TECHNOLOGY & ENGINEERING / Mobile & Wireless Communications; FiWi access networks; Wireless communication systems; FiWi access networks; FiWi access networks; Wireless communication systems; Electronic books